Hidden negative linear compressibility in lithium l-tartrate - Yeung, H; Kilmurray, R; Hobday, C; McKellar, S; Cheetham, A; Allan, D; Moggach, S (Royal Society of Chemistry, 2017)
Development of artificial muscles, next-generation pressure sensors and precision optics relies on advances in materials with anomalous mechanical properties. Negative linear compressibility, NLC, is one such rare, counterintuitive phenomenon, in which a material expands along one axis under hydrostatic pressure. Both classical and recent NLC materials face a pay-off between the active pressure range and magnitude of NLC, and in the vast majority of cases the NLC effect decreases with pressure. By decoupling the mechanical behaviour of building units for the first time in a winerack framework containing two different strut types, we show that lithium L-tartrate exhibits NLC with a maximum value, Kmax = -21 TPa^-1, and an overall NLC capacity, χNLC = 5.1 %, that are comparable to the most exceptional materials to date. Furthermore, the contributions from molecular strut compression and angle opening interplay to give rise to so-called “hidden” negative linear compressibility, in which NLC is absent at ambient pressure, switched on at 2 GPa and sustained up to the limit of our experiment, 5.5 GPa. Analysis of the changes in crystal structure using variable-pressure synchrotron X-ray diffraction reveals new chemical and geometrical design rules to assist the discovery of other materials with exciting hidden anomalous mechanical properties.